Experimental Study of The Growth of Ammonium Bisulfate Ash Deposition at Different Wall Temperatures and Heat Transfer Characteristics - Yu Yongfei; Pan Weiguo (E3S Web of Conferences)
The deposition of ammonium bisulfate ash (ABS) is a common occurrence in the flue of a boiler in a power plant. This can result in a reduction in the efficiency of the selective catalytic reduction (SCR) process and the air preheater. To reduce the formation of ABS deposits in flue gas systems, extend the service life of SCR catalysts, and improve the efficiency of heat exchangers, online monitoring technology was employed to observe the formation of ABS deposits in a vertical one-dimensional furnace. The objective of this study is to investigate the formation of ABS deposits on heat transfer surfaces at varying temperatures and their impact on heat transfer characteristics. It was observed that the growth rate of ABS deposition decreased with the increase in wall temperature. At temperatures of 250°C, 300°C, and 350°C, the stable thickness of ABS deposition decreased to 4.09mm, 3.97mm, and 3.84mm, respectively. Moreover, the relative heat flux (RHF) also increases with the increase of wall temperature, from 0.68 at 250°C to 0.78 at 350°C. Consequently, an increase in the surface temperature of the heat transfer medium can effectively reduce the formation of ABS deposits and enhance the efficiency of heat transfer.